Altered metabolomics and inflammatory transcriptomics in human bone marrow adipocytes after acute high calorie diet and acute fasting - Costa, Samantha N.; Pachón-Peña, Gisela; Dragon, Julie; Tighe, Scott; Vary, Calvin; Fazeli, Pouneh K.; Bredella, Miriam A.; Rosen, Clifford J. (Frontiers in Endocrinology, 2025)
Expansion of bone marrow (BM) adipocytes has been linked to nutritional pressures, suggesting that BM is a dynamic compartment that responds to fluctuations in systemic nutritional availability to regulate osteogenesis and hematopoiesis. Here, we investigated BM metabolism in response to acute overnutrition (high calorie diet; HCD) and calorie deprivation (fasting). Participants underwent a 10-day HCD followed by a two-week interval of an ad libitum diet and then underwent 10 days of fasting. BM adipocytes and sera were collected before and after each dietary intervention for each participant. Using comprehensive and integrated analyses, we characterized nutritional influences on BM adiposity. BM adipocytes after HCD showed an upregulation of FOXP3, the transcription factor that controls the development of Tregs, which are critical in reducing inflammatory immune responses. After fasting, BM adipocytes had an upregulation of inflammatory genes (CP, CFH, VCAN, and IGFBP3). Proteomic analysis after HCD showed that BM serum had an upregulation of proteins related to an inflammatory/complement pathway. After fasting, in the BM serum, there was a significant downregulation of inflammatory/complement pathway proteins. Despite both interventions causing BM adipose tissue expansion, the mechanism for adipogenesis appears to be dependent on nutrient availability. After HCD, lipid-mediated signaling and lipid storage, and lipid droplet biogenesis were significantly downregulated. In contrast, after fasting, lipid-mediated signaling and lipid storage, and lipid droplet biogenesis were significantly upregulated. Overall, our results demonstrate key differences in inflammatory response and lipid metabolism between HCD and fasting, despite a nearly identical BM adipose phenotype. Further analyses are needed to understand the effects nutritional pressures have on BM adipogenesis and immune responses.